Analisis Yuridis Terhadap Tipologi Kejahatan Konvensional dan Transnasional pada Kasus TPPO NTT–Malaysia Tahun 2024 - Destriani Silla; Yufitris Naitboho; Oktovina Mopia; Dato Abdul Aziz; Mark Jhon Bilistolen; Natalia Stefania Beka; Maria Jesnita Melania Lao; Irfan Harbona Ollo; Maria Fransiska Mika; Arki Artaban Sae; Selfi Theorin Kasse; Fadil Mas’ud; Kevy Listiana Fransisca Taneo (CV Rewang Rencang, 2025)
This study explores various traditional and cross-border crimes, focusing on Indonesia and Malaysia's legal cooperation to combat human trafficking in 2024. Using a legal approach based on laws and regulations, the research reveals both countries have employed tools like Mutual Legal Assistance, ACTIP, and treaties to collaborate. However, challenges persist including differences in legal systems, slow government processes, and limited resources. The study recommends improving legal harmonization and leveraging technology to enhance coordination, thereby strengthening crime handling and victim protection efforts.